Water-dispersible polyaniline/graphene oxide counter electrodes for dye-sensitized solar cells: Influence of synthesis route on the device performance. (1st September 2020) - Lemos, Hugo G.; Barba, David; Selopal, Gurpreet S.; Wang, Chao; Wang, Zhiming M.; Duong, Adam; Rosei, Federico; Santos, Sydney F.; Venancio, Everaldo C.
Graphical abstract: Highlights: Water-dispersible PANI-GO is tested as counter-electrodes (CEs) in DSSCs. PANI-GO-0.45-In situ CE based DSSC shows power conversion efficiency of about 20% higher than Platinum-CE. The synthesis route of PANI-GO nsnocomposites strongly influences the DSSC performance. Abstract: The fabrication of efficient and platinum-free counter electrodes (CE) is a highlighted topic for the development of advanced dye-sensitized solar cells (DSSCs). Here, we developed water-dispersible polyaniline/graphene oxide (PANI-GO)-based CEs, which can be straightforwardly prepared by deposition of the nanocomposite dispersion onto FTO substrate. The water-dispersibility properties of PANI-GO allow the formation of smooth films without organic solvents making it a promising material for high-scalable, reduced cost and 'greener' fabrication of energy conversion-storage devices. Aqueous dispersions of PANI-GO nanocomposites were prepared by two different routes: physical mixture of PANI and GO, and in situ polymerization of aniline in GO aqueous dispersion. DSSC assembled with emeraldine salt polyaniline (PANI-ES)-based CE generated current density (Jsc ) of 12.37 mA/cm 2 and power conversion efficiency (PCE) of 5.09%, which was comparable to the device prepared with Pt-based CE (PCE of 5.15%). The addition of GO is found to increase the Jsc to 12.91 mA/cm 2 and the fill factor to 67% in CE containing 0.45 wt% of GO (in respect to aniline during synthesis) where the PCE is boosted to 6.12%, which is about 20% higher than Pt-based CE. The investigation of both morphological features and spectroscopic properties showed that PANI-GO nanocomposites prepared by in situ route have dissimilar protonation and oxidation states when compared with those prepared by physical mixture route. These results give insights into the role of GO in tuning PANI chemical and physical properties. Also offers a simpler and more efficient methodology for the synthesis of new CEs for DSSCs.